KURIKULUM DAN KOEDUKASI PENDIDIKAN ISLAM (Pandangan Abu Al-Hasan Al-Qabisi Dan Rasyid Ridha) - Muh Iqbal (Jurnal Teknologi Pendidikan Madrasah, 2019)
Religious education should color the personality of students so that religion is concrete as part of the personality that is controlling in his life. Islamic Education reformers and thinkers respond to education curricula and coeducation with diverse views. Abu al-Hasan al-Qabisi and Rasyid Ridha are two Islamic Education thinkers who have a significant view of the two objects of this education study. Coeducation means "co educational class" which means mixing between men and women in a class, an education system that is carried out through a teaching and learning process that combines men and women in a room (class), or often also known as mixed education. While the Islamic education curriculum is an integral part that is very vital in achieving educational outcomes or goals. The implementation of a coeducation system in Islamic education for al-Qabisi that not both boys and girls mix in a class, because it is feared morally damaged, the separation of places of education must be done for the sake of safeguarding children from moral deviations. While Rashid Ridha rejects the existence of the benefits of coeducation, and considers that coeducation does not only have deficiencies, but can bring havoc, especially women.